Effect of pot size and growing media on seedling vigour of four indigenous tree species under semi-arid climatic conditions. Issue 1 (2nd January 2018) - Abera, Binyam; Derero, Abayneh; Waktole, Samson; Yilma, Getaw
Abstract: Appropriate nursery and tree planting technologies are vital for successful afforestation and reforestation. Seedlings of four important indigenous fodder and fruit tree species, Acacia nilotica, Acacia tortilis, Dobera glabra and Ziziphus spina-christi, were grown in three different levels of polybag pot size (8, 10 and 15 cm) and three different soil mixes (local topsoil, manure and sand). The experiment was implemented in a factorial randomized complete block design at the semi-arid Werer Center in the southern Afar, Ethiopia. Seedling height and root collar diameter were measured from second to seventh month after seed sowing. The results showed that seedlings raised in large pots had significantly greater height and root collar diameter, than those raised in the other two container types. On the contrary, there was no effect of the soil mix. We thus recommend the use of large polybag pots for seedling production in semi-arid areas as this will ensure greater success in tree establishment, though this may mean higher initial cost.